Calculation and Analysis of Vibration Stress of Guangxi Nanning Subway during Operation. (2nd February 2022) - Chang, Zhenchao; Luo, Junhui; Wang, Shihai; Huang, Haifeng; Mo, Peng; Wu, Chunwei; Liao, Laixing; Chen, Yuanpeng; Huang, Mian; Wu, Yuhang
Abstract : In this study, based on the Mindlin solution in elastic half-space, the stress calculation formula was determined with consideration of any point in the foundation under the dynamic amplification effect. The train load was simplified as a concentrated force moving in the direction of the train, and the stress of the soil under a single wheel load was analyzed. In the state, σ z reached a maximum value of 0.56 kPa when the axle was directly above the soil, and the stress decreased until it approached zero as the distance from the soil unit increased. Then, taking the Nanning Metro Line 1 as an example, the load was regarded as the superposition of several single-wheel loads, and the law of the soil stress change at a point directly below the moving line of the train load at different axle loads, speeds, and burial depths was studied. From the analysis of the results, it could be seen that the soil stress under different working conditions was always proportional to the train axle load, speed, and burial depths. The peak stress ratio corresponding to the depths of 9 m, 12 m, and 15 m was 1:2:11, indicating that the closer the load to the soil, the more significantly the stress of the soil element increased. Under multiple wheel loads, the soil stress always exhibited continuous cycle characteristics. The cycle period was related to the time it took for the metro to pass through the point in the soil, and the cycle period was the ratio of the distance between each axle and the vehicle speed.